Tunneling in limestone rock using TBM method for MRT projects near cochrane station - Pauzi N.I.M.; Radhi M.S.M.; Wong L.S.; Omar H. (E-Journal of Geotechnical Engineering, 2023)
Tunnel construction in Kuala Lumpur area are to be build due to the increasing traffic congestion in urban areas and increasing land price. Underground structure like tunneling can preserve the land above while providing a route for Mass Rapid Transport (MRT) line for transportation. MRT line in Kuala Lumpur area starts from Sungai Buluh transverse to Kajang. A Cochrane station was to be built underground at the limestone area. TBM method is used for tunneling. A total of 10 TBMs will be used for the construction of tunnels for the 9.5 km underground portion of the Sungai Buluh to Kajang line. The borehole logging method of the area reveals that the limestone rocks of the area have low to moderate strength with approximately 48 MPa to 74 MPa which was determined by unconfined compressive strength test. There are three methods of construction for tunneling such as NATM, cut and cover and rock blasting. It is practically good to used TBM method for tunneling in limestone rock. TBM was designed to handle excavation through the different geological formation. The transitions between the two geological formations in Kuala Lumpur area are such as Kenny Hill formation and karstic limestone are easier by TBM method of underground excavations. The tunneling excavation using TBM was the most suitable for Kuala Lumpur limestone area which have low to moderate strength limestone. TBM has the advantages and disadvantages depending on the type of geological found in that area. Some unforeseen geological condition may delay the rate of penetration of TBM. These unforeseen geological condition may imposed higher cost for the TBM to be repaired. This paper discussed on the suitability of TBM as method of tunneling excavations in limestone rock for underground construction of Cochrane station. © 2014, EJGE.